Corporate Culture as a Tool for Effective Management of the Enterprise to Improve its Competitiveness (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The conceptual foundations of corporate culture summarized the views of different scholars, and defined role and place in the organization management, market relations and competitiveness were investigated in the article. Attention is focused on the transformation processes in the economy made by people who have their own system of values, rules, norm of conduct, management models that include the concept of corporate culture. The main tools to improve competitiveness should be directed on the human factor, the study of the phenomenon of corporate culture today, cut off from the academic knowledge to the necessary component of practice. Researched and summarized importance of corporate culture as a tool for effective management and its impact on competitiveness and creating a positive image of the organization. Revealed the mechanism of its formation, structure, types and functions. Discovered and proved the impact of the national mentality on development of corporate culture, its effectiveness analyzes. Based on the study of scientific literature on this subject there were identified problems and obstacles to implementing corporate values and stressed the need for their widespread introduction.
Keywords: corporate culture, corporate governance, competitiveness, strategic competitive advantage tool management, image